2011
DOI: 10.1111/j.1540-5885.2011.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking Innovation to Design: Consumer Responses to Visual Product Newness

Abstract: In recent years, researchers have begun to recognize the central role that visual design plays in successful marketing efforts. However, little research has effectively bridged the gap between product innovation and visual design. Before consumers can judge the competitive newness of a product based on its functionality, they first encounter its visual form. Therefore, both innovation researchers and product managers need to be aware of the impact that visual design can have in communicating product newness. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 39 publications
(49 reference statements)
2
127
0
10
Order By: Relevance
“…In fact, Radford and Bloch (2011) was unable to identify a specific visual attribute that constitutes design newness, suggesting that solely attributing newness to the design itself cannot adequately account for a product's design newness. Additional evidence has shown that consumers respond differently to design newness.…”
Section: Review Of Relevant Literature and Theoretical Framework Desimentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, Radford and Bloch (2011) was unable to identify a specific visual attribute that constitutes design newness, suggesting that solely attributing newness to the design itself cannot adequately account for a product's design newness. Additional evidence has shown that consumers respond differently to design newness.…”
Section: Review Of Relevant Literature and Theoretical Framework Desimentioning
confidence: 99%
“…Consistent with this idea, consumers exhibit more positive affective reactions and aesthetic evaluations toward products with higher levels of design newness, but what the specific affective response is has not been examined (Radford & Bloch, 2011). Appraisal theories of emotions propose that all emotions are evoked by a set of cognitive appraisal (Ellsworth & Smith, 1988;Scherer, 1999;Smith & Ellsworth, 1985).…”
Section: Emotional Responses To Perceived Design Newnessmentioning
confidence: 99%
See 3 more Smart Citations